2013
DOI: 10.1016/j.amepre.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Control in Latin American and U.S. Latinos

Abstract: Context-Latinos are the largest and fastest-growing ethnically diverse group in the U.S.; they are also the most overweight. Mexico is now second to the U.S. in experiencing the worst epidemic of obesity in the world. Objectives of this study were to (1) conduct a systematic review of obesity-related interventions targeting Latinos living in the U.S. and Latin America and (2) develop evidence-based recommendations to inform culturally relevant strategies targeting obesity.Evidence acquisition-Obesity-related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…Obesity is a leading risk factor for cardiovascular disease, and its global prevalence has more than doubled since the 1980s . Latin Americans are at high risk , with rapid expansion of obesity and cardiovascular disease in the context of accelerating urbanization. This study's participants are from Chile, where dramatic socioeconomic improvement accompanied by changes in diet, physical activity and sociocultural environment has resulted in obesity prevalence among the highest in the world .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a leading risk factor for cardiovascular disease, and its global prevalence has more than doubled since the 1980s . Latin Americans are at high risk , with rapid expansion of obesity and cardiovascular disease in the context of accelerating urbanization. This study's participants are from Chile, where dramatic socioeconomic improvement accompanied by changes in diet, physical activity and sociocultural environment has resulted in obesity prevalence among the highest in the world .…”
Section: Introductionmentioning
confidence: 99%
“…39 Latino children are also amongst the most overweight and obese ethnic group of children in the United States. 1, 39 For example, the National Survey of Children’s Health study found that 47% of Latino children are overweight and 31% are obese, compared to 35% and 21%, respectively, for white children.…”
Section: Introductionmentioning
confidence: 99%
“…39 Latino children are also amongst the most overweight and obese ethnic group of children in the United States. 1, 39 For example, the National Survey of Children’s Health study found that 47% of Latino children are overweight and 31% are obese, compared to 35% and 21%, respectively, for white children. 1 In addition, while the U.S. leads in the prevalence of overweight and obesity globally, Mexico is now second to the U.S. in experiencing the worst epidemic of childhood obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, where healthcare professionals hold a respected position, this setting may exert a strong influence on patients' behaviours (Holub et al, 2013). Physical activity can be effectively applied in practice for disease prevention and treatment in healthcare settings (Meyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%